2006
DOI: 10.1016/j.atherosclerosis.2005.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Major role of HSP70 as a paracrine inducer of cytokine production in human oxidized LDL treated macrophages

Abstract: Lipid accumulation and inflammation are key hallmarks of the atherosclerotic plaque and macrophage uptake of oxidized low-density lipoprotein (oxLDL) is believed to drive these processes. Initial experiments show that supernatants from oxLDL treated macrophages could induce IL-1β production in naïve macrophages. To search for potential paracrine mediators that could mediate this effect a DNA microarray scan of oxLDL treated human macrophages was performed. This analysis revealed that oxLDL induced activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…For example, HSP70 can bind toll-like receptors 2 and 4 (TLR-2 and -4) and thereby induce NFB activation, IL-6 production, as well as the secretion of IL-1␤ and IL-12-both proinflammatory cytokines. 22,33 Other reports show that SR-A is capable of binding Gp96, an endoplasmic reticulum-bound HSP on antigen presenting cells. 34 However, we now show that HSP27 may have effects opposite to those observed for other extracellular HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HSP70 can bind toll-like receptors 2 and 4 (TLR-2 and -4) and thereby induce NFB activation, IL-6 production, as well as the secretion of IL-1␤ and IL-12-both proinflammatory cytokines. 22,33 Other reports show that SR-A is capable of binding Gp96, an endoplasmic reticulum-bound HSP on antigen presenting cells. 34 However, we now show that HSP27 may have effects opposite to those observed for other extracellular HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have also reported that extracellular HSP70 could stimulate the production of anti-inflammatory cytokine IL-10 in responsive T cells (Wendling et al 2000) and attenuate the intimal thickening in mice exposed to cigarette smoke (Matsumoto et al 2008). In contrast, some conflicting reports showed the adverse effects of circulating HSP70 as a paracrine inducer of proinflammatory cytokines, especially IL-6, which exacerbate the inflammatory process in the development of atherosclerosis plaques (Asea et al 2000;Gonzalez-Ramos et al 2013;Svensson et al 2006). HSP70 serum concentration was also shown to increase in patients with peripheral atherosclerosis according to some epidemiological investigations (Wright et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The immune system also appears to recognize other by-products of macrophage activation, such as heat shock proteins (Hsp) [16]. Hsp are also immunogenic [17], and are also able to activate macrophages through interactions with Toll-like receptors [18] and lipid rafts [19,20]. Therefore, a variety of circuits are activated by modified lipoproteins and mLDL-IC, setting the conditions for a chronic inflammatory reaction in the vessel walls.…”
Section: Introductionmentioning
confidence: 99%